Electoral Politics: Democracy and Electoral Security in Nigeria - Idowu, Olusegun Oladele (African Journal of Stability and Development (AJSD), 2023)
Democracy in Nigeria has been fragile and fluctuating since independence as conflict, triggered by political rivalries, violence, ethnicity, religion and insecurity, poses a major threat to her democracy. The late Nigerian political scientist and theorist, Claude Ake in 1993, warned that external and elite support for electoral democratisation was not the same as actual democracy. He argued that the substitution of democracy for elections had resulted in a struggle for power at the polls by the elite groups. To this end, the incidences of electoral violence, political competition and insecurity have since become a constant nightmare and a serious source of concern to all actors participating in the electoral system. The cornerstone of democracy is the electoral process, with a viable Election Management Board (EMB) that conducts free, fair, open and secured elections. Electoral security is one of the focal points for a successful and effective administration of the electoral process. The electoral process must be geared towards building citizens' confidence, especially by ensuring that votes are cast anonymously and without coercion, while also making sure that election results reflect the collective will of the voters. With the aid of secondary sources of data, using content analysis, the paper concludes that defending elections not only involves protecting voting units and ballots, but also protecting the functions, resources and technologies that support election processes and which help manage voters and election results in Nigeria. In order to protect our electoral politics in Nigeria, there is a need for an effective and secure electoral process, laced with a credible and acceptable outcome. This paper emphasises on security as a crucial condition in the context of elections, such that it assists in establishing an enabling environment that is conducive to holding democratic polls.